ответ:
пошаговое объяснение:
-3 1\2: (-1 2\3-3 1\12) и 5\18*(-1 5\7)+1 3\14
-3 1\2: (-1 2\3-3 1\12)= -7/2: (-5/3-37/12)=-7/2: (-20/12-37/12)=-7/2: (-57/12)=
=-7/2*(-12/57)=42/57
5\18*(-1 5\7)+1 3\14=5/18*(-12/7)+17/14=-10/21+17/14= -40/84+102/84=
=62/84=31/42
42/57 меньше 31/42
ответ:
пошаговое объяснение:
-3 1\2: (-1 2\3-3 1\12) и 5\18*(-1 5\7)+1 3\14
-3 1\2: (-1 2\3-3 1\12)= -7/2: (-5/3-37/12)=-7/2: (-20/12-37/12)=-7/2: (-57/12)=
=-7/2*(-12/57)=42/57
5\18*(-1 5\7)+1 3\14=5/18*(-12/7)+17/14=-10/21+17/14= -40/84+102/84=
=62/84=31/42
42/57 меньше 31/42